Lire les yeux dans le théâtre de Pierre Corneille - Fusacchia, Federica (Verbum – Analecta Neolatina, 2025)
From the 17th century onwards, the actors’ physical movements on stage were reflected in a constant struggle and exchange of glances, with the eyes as the main means of transmission. They thus became active characters in the play, really dramatic individuals. In this sense, this study aims to evaluate the importance of the lexeme yeux in classical French theatre, particularly in Cornelian plays, where this term frequently recurs and even becomes a main character in its own right. Statistical linguistics research was carried out on all the plays written by Corneille in order to study this aspect. This made it possible to create graphs for analysing the lexeme yeux and other terms linked to the lexicon of sight.